2014
DOI: 10.1016/j.jpeds.2014.01.053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prenatal Methamphetamine Exposure on Behavioral and Cognitive Findings at 7.5 Years of Age

Abstract: Objective To examine child behavioral and cognitive outcomes after prenatal exposure to methamphetamine. Study design 412 mother-infant pairs (204 methamphetamine-exposed and 208 unexposed matched comparisons) were enrolled in the Infant Development, Environment and Lifestyle (IDEAL) study. The 151 children exposed to methamphetamine and 147 comparisons who attended the 7.5 year visit were included. Exposure was determined by maternal self-report and/or positive meconium toxicology. Maternal interviews asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 35 publications
0
41
0
4
Order By: Relevance
“…Most studies of prenatal methamphetamine have focused on the impact of this drug on behavior and cognitive effects during early childhood. Prenatal methamphetamine produces a variety of neurological effects, including structural changes in the brain (8,37), increased prevalence of cognitive and behavioral problems (11,23), delayed development of gross motor skills (42), and decreased verbal and spatial memory (8). In contrast to these neurological effects, the impact of prenatal methamphetamine exposure on the adult cardiovascular system has not been well studied.…”
mentioning
confidence: 99%
“…Most studies of prenatal methamphetamine have focused on the impact of this drug on behavior and cognitive effects during early childhood. Prenatal methamphetamine produces a variety of neurological effects, including structural changes in the brain (8,37), increased prevalence of cognitive and behavioral problems (11,23), delayed development of gross motor skills (42), and decreased verbal and spatial memory (8). In contrast to these neurological effects, the impact of prenatal methamphetamine exposure on the adult cardiovascular system has not been well studied.…”
mentioning
confidence: 99%
“…These smoking rates are elevated when compared to WA data which show 12% of pregnant women smoke in pregnancy [12,14]. Smoking in pregnancy has serious long-term health implications for women and their babies [15]; it increases the woman's risk of spontaneous abortions, placental abruption, cardiovascular and pulmonary disease. Adverse foetal outcomes associated with smoking in pregnancy include; preterm delivery, sudden infant death syndrome and low birth weight [1,8,14,16,17].…”
Section: Discussionmentioning
confidence: 93%
“…However, there was a significant group by gender interaction for the right (p=0.002) but not left (p=0.138) relative hippocampal volume. Follow-up independent sample t test of right hippocampus relative volume found that: 1) there was a significant subgroup difference between female patients and female controls (t (16) =2.915, p=0.010) but such a difference did not exist between male patients and male controls (t (36) = −0.929, p=0.359) (Figure 2); 2)there was a significant subgroup difference between male controls and female controls (t (27) = −4.443, p<0.001) but there was no such a difference between male patients and female patients (t (25) = −0.014, p=0.989) (Figure 3). …”
Section: Resultsmentioning
confidence: 99%
“…Cognitive dysfunction in MA users, especially memory impairment, has been reported widely (5, 14, 16). It has been suggested that hippocampus might be involved in MA-related cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%